2011
DOI: 10.1002/jor.21509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treadmill running on rat gastrocnemius function following botulinum toxin A injection

Abstract: Exercise can improve and maintain neural or muscular function, but the effects of exercise in physiological adaptation to paralysis caused by botulinum toxin A has not been well studied. Twenty-four rats were randomly assigned into control and treadmill groups. The rats assigned to the treadmill group were trained on a treadmill three times per week with the running speed set at 15 m/min. The duration of training was 20 min/session. Muscle strength, nerve conduction study and sciatic functional index (SFI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…In this study, rats with VML injured muscle repaired with a porcine UBM scaffold were subjected to physical rehabilitation (i.e., voluntary wheel running) beginning either one week or four weeks postinjury. Physical rehabilitation has been shown to foster regeneration of injured muscle using muscle grafts [7,56,57], and is postulated to improve ECM mediated tissue remodeling [42,58,59]. However, in this study, regardless of the time of initiation of physical rehabilitation, neither muscle fiber regeneration nor function of the porcine UBM scaffold repaired muscles improved compared to no rehabilitation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In this study, rats with VML injured muscle repaired with a porcine UBM scaffold were subjected to physical rehabilitation (i.e., voluntary wheel running) beginning either one week or four weeks postinjury. Physical rehabilitation has been shown to foster regeneration of injured muscle using muscle grafts [7,56,57], and is postulated to improve ECM mediated tissue remodeling [42,58,59]. However, in this study, regardless of the time of initiation of physical rehabilitation, neither muscle fiber regeneration nor function of the porcine UBM scaffold repaired muscles improved compared to no rehabilitation.…”
Section: Discussioncontrasting
confidence: 54%
“…It is possible that a different modality or a prescribed running regimen may elicit performance improvements. However, in recognition of the literature [7,56,57], the current results underscore that the efficacy of physical rehabilitation is likely to increase synergy only when appreciable de novo muscle tissue regeneration is realized.…”
Section: Discussionmentioning
confidence: 67%
“…Studies showed that muscle mass following BoNT-A injection was reduced by approximately 70% to 30% within 1 to 6 months [8284]. A 30% to 90% (approximately) reduction in muscle force was reported in animal studies [83, 8587].…”
Section: Changes In Muscle Physiology Neuromuscular Junction Andmentioning
confidence: 99%
“…The reduction in CMAP parallels the decrease in the mean rectified voltage during a maximal voluntary contraction [101]. A recent study showed that the CMAP amplitude was significantly reduced, while no changes of distal latency were found in the gastrocnemius following a BoNT-A injection for 4 weeks [84]. This result was compatible with the results of a previous study demonstrating that an injection of BoNT-A caused localized muscle paralysis but no disruption in axonal transport [102].…”
Section: Changes In Muscle Physiology Neuromuscular Junction Andmentioning
confidence: 99%
See 1 more Smart Citation